2019
DOI: 10.3390/ma12203399
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Biodegradation of Cellulose Fiber Blends with Incorporated ZnO

Abstract: This research aimed to study the influence of lyocell with incorporated ZnO (CLY) for antibacterial activity and biodegradation of fiber blends composed of viscose (CV), flax (LI), and CLY. Fiber blended samples with an increased weight fraction of CLY fibers were composed, and single CLY, CV and LI fibers were also used for comparison. Antibacterial activity was determined for the Gram-negative Escherichia coli and the Gram-positive Staphylococcus aureus bacteria. The biodegradation of fiber blends was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The mechanism for antimicrobial effect is not well known, although it could be due to the binding of ZnO particles on the bacterial surface through electrostatic forces [47], disruption of cell membrane with loss of its functionality [48], and generation of hydrogen peroxide [49]. It was demonstrated that the ZnO nanoparticles structure, chemical composition and morphology play a crucial role in antimicrobial activity [50]: Zn 2+ cations, released from ZnO nanorods dissolution in water, are able to interact with different bacterial target sites [51,52]. The higher surface area of nanostructures with respect to that of bulk materials can promote a faster ion release in water or physiological solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for antimicrobial effect is not well known, although it could be due to the binding of ZnO particles on the bacterial surface through electrostatic forces [47], disruption of cell membrane with loss of its functionality [48], and generation of hydrogen peroxide [49]. It was demonstrated that the ZnO nanoparticles structure, chemical composition and morphology play a crucial role in antimicrobial activity [50]: Zn 2+ cations, released from ZnO nanorods dissolution in water, are able to interact with different bacterial target sites [51,52]. The higher surface area of nanostructures with respect to that of bulk materials can promote a faster ion release in water or physiological solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The outstanding antimicrobial activity of the PCL/CS/ZnO composite coating was due to the synergistic antimicrobial properties of CS and ZnO NPs. This result in the production of reactive oxygen species (ROS) like H 2 O 2 , where CS electrostatically binds to the bacterial cell wall while ZnO NPs interact with protein membrane, resulting in the intracellular released material and perforated cell membrane [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Antibacterial Studiesmentioning
confidence: 99%
“…These include some of the oldest man-made materials, such as textiles. Today, the word design is more relevant to them than ever before, because smart textiles have a great future utilization in healthcare [1][2][3], medicine [4][5][6][7][8], transport [9,10], sports and leisure [11,12], safety and personal protective equipment [13], construction [14], interior design [15,16], agriculture [17], sensors and biosensors [18][19][20], etc. Materials creation is associated with combining their known properties with new functionality to ensure active interaction with the environment, i.e., ability to react and adapt to changes [21].…”
Section: Introductionmentioning
confidence: 99%